Leave – Stay – Return: Understanding Mobility Trajectories of German Migrants by Choice Moving to and from Canada - Patzelt, Anke (Université d'Ottawa / University of Ottawa, 2021)
This dissertation focuses on the mobility trajectories of highly skilled and relatively affluent migrants who move between highly developed countries of the “global North”. While these “migrants by choice” are often seen as “desired immigrants” who hold the privilege to move internationally relatively unrestricted, little is known about their actual migration decision-making behaviour and their lived experiences in their place(s) of destination. To address this research gap, I explore the migration trajectories of German migrants by choice moving to and from Canada as a case study. Drawing on 48 narrative life story interviews with Germans at different stages of their migration trajectories (i.e., the pre-movement phase, the phase of settling down and living in Canada and the phase of return and/or onward movement) I specifically analyse a) their lived experiences in their day-to-day life (including experiences of settlement and integration as well as the place attachments they form during their mobility trajectories to b) understand how these experiences impact their decisions of leaving, staying, returning, or moving onward, i.e., to be internationally mobile. The results demonstrate that emotional or ideational reasons as well as chance were the main drivers behind my interviewees’ movements to Canada. Moreover, the findings underline that migration decisions are often formed in ongoing processes that change and evolve over time and are closely tied to my interviewees’ lived experiences at their local places of destination as well as significant life course events, such as the birth of a child or relationship break-up. Drawing on these findings, I ultimately propose a new and comprehensive model explaining the migration decision-making processes of migrants by choice. In doing so, this dissertation makes five important contributions to the field of migration and mobility studies, namely 1) it challenges the sedentary bias in migration studies; 2) it underlines the importance of moving away from strictly national or transnational perspectives on migration movements; 3) it highlights the importance of considering the lived experiences as well as the challenges and hidden frictions of highly skilled migration movements; 4) it challenges a purely economic or political understanding of migration processes; and 5) it highlights the importance of exploring the dissonance between policy intentions and the actual behaviour of migrants.
Keywords: Migrants by choice; Mobility; Migration decision making; Step-by-step immigration; Germany; Canada